2011
DOI: 10.1002/jmri.22450
|View full text |Cite
|
Sign up to set email alerts
|

Prostate T1 quantification using a magnetization‐prepared spiral technique

Abstract: Purpose: To adapt a magnetization-prepared spiral imaging technique, termed T1prep, for time-efficient radiofrequency (RF)-insensitive prostate T 1 quantification at 1.5 T and evaluate signal-to-noise ratio (SNR) limits to voxelbased versus subregion analysis. Materials and Methods:A magnetization-prepared spiral imaging technique was adapted for robust T 1 contrast development, multislice imaging within 5 minutes, and data regression to a monoexponential decay. In vitro testing evaluated RF insensitivity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
1
7
1
Order By: Relevance
“…However, at 7 T the in vivo T 2 values reported by Scheenen et al (Scheenen et al , 2011) for young healthy volunteers were notably lower (PZ: 64 ms, transition zone: 50 ms). In this study it was found that T 1 , T 2 and ADC were higher in CG than PZ (significantly so for T 2 ), which is in contradiction to previous data (Gibbs et al , 2001; Foltz et al , 2011; Foltz et al , 2010a; Scheenen et al , 2011) where PZ exceeded CG in all parameters. However, while at 1.5 T T 1 was higher in PZ than CG (Foltz et al , 2011), in 7 T T 1 -weighted in vivo imaging there was no contrast between PZ and CG in (Scheenen et al , 2011).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, at 7 T the in vivo T 2 values reported by Scheenen et al (Scheenen et al , 2011) for young healthy volunteers were notably lower (PZ: 64 ms, transition zone: 50 ms). In this study it was found that T 1 , T 2 and ADC were higher in CG than PZ (significantly so for T 2 ), which is in contradiction to previous data (Gibbs et al , 2001; Foltz et al , 2011; Foltz et al , 2010a; Scheenen et al , 2011) where PZ exceeded CG in all parameters. However, while at 1.5 T T 1 was higher in PZ than CG (Foltz et al , 2011), in 7 T T 1 -weighted in vivo imaging there was no contrast between PZ and CG in (Scheenen et al , 2011).…”
Section: Discussioncontrasting
confidence: 99%
“…In line with expectation, the T 1 times were substantially longer at 7 T than those reported at 1.5 T (Foltz et al , 2011), and the T 2 values were comparable to those reported at lower field strength (Foltz et al , 2010a; Gibbs et al , 2001; Langer et al , 2009). However, at 7 T the in vivo T 2 values reported by Scheenen et al (Scheenen et al , 2011) for young healthy volunteers were notably lower (PZ: 64 ms, transition zone: 50 ms).…”
Section: Discussionsupporting
confidence: 90%
“…In 1987, Kjaer et al were not able to detect significant differences in T1 between PCa and benign prostate hyperplasia in 18 patients using six inversion recovery sequences with a fixed TR and different inversion times (TI) and a 1.5 T magnet 15 . Foltz et al found significantly shorter T1 in PCa lesions compared to normal appearing prostate tissue in 13 patients using a magnetization-prepared spiral technique and a 1.5 T magnet 16 . More recently, Ma et al used MR fingerprinting 36 and a 3 T magnet to quantitatively measure T1 on non-contrast-enhanced MRI in 109 PCa lesions and normal appearing prostate tissue in the PZ 17 .…”
Section: Discussionmentioning
confidence: 99%
“…In the context of cardiovascular imaging, T1 mapping has been established as an essential tool for characterization of myocardial tissue including the quantification of amyloidosis and detection of inflammatory myopathy 13,14 . Few studies have evaluated its value for prostate imaging with mixed results using different technical approaches [15][16][17] .…”
mentioning
confidence: 99%
“…In addition, although not often reported, we observed a small, but statistically significant, difference between the mean T 1values of cancerous and noncancerous regions consistent with a recent publication. 36 For individual sequence evaluation, the order in terms of performance was ADC > DCE > NT2W > T 1 as seen in Fig. 7.…”
Section: Discussionmentioning
confidence: 98%